The effect of novel flax oil-based implant coating on bone healing process (in vivo animal study) - Mustafa, Nazih Shaban; Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon (ELSEVIER, 2015)
Objective This pilot study was designed to investigate the effect of new implant coating material on ‎postoperative bone healing process.‎